Implementasi Bandwidth Manajemen menggunakan Mikrotik dengan Metode Per Connection Queue di Gedung Perkuliahan Universitas Nahdlatul Ulama Kalimantan Selatan: Implementation of Bandwidth Management using Mikrotic with Per Connection Queue Method in the Lecture Building of Nahdlatul Ulama University of South Kalimantan - Sofyar, Sofyar; Risdayati, Sunni; Andini, Yulia (Nusantara Journal of Science and Technology, 2024)
The purpose of this study is to optimize the use of internet network resources by distributing bandwidth fairly and evenly, stabilizing the internet network so that users can download and upload with evenly distributed bandwidth consumption, and avoiding overloading of internet network access usage. In conducting the study, the author collected primary and secondary data needed to implement bandwidth management on the internet network in the lecture building of the Nahdlatul Ulama University of South Kalimantan (Unukase) campus. This study also analyzed the hardware and software needs as supporting tools for implementing bandwidth management in the Unukase Lecture Building. The research that the author uses is NDCL (Network Development Life Cycle) which is a model that defines the process cycle in building an internet network system, NDLC has elements that define phases, stages, steps, or process mechanisms specifically. The test results after implementing bandwidth sharing with PCQ (Per Connection Queue), that all users access download more evenly by getting 5Mbps, and for upload access, all users get almost 5Mbps.